Vibrations and bending of thin laminated square plates with holes in gradient elasticity: A finite element solution. (February 2023) - Bacciocchi, M.; Fantuzzi, N.; Neves, A.M.A.; Ferreira, A.J.M.
Abstract: Nonlocal elasticity is becoming more and more popular due to the introduction of advanced constituents and the need of a peculiar approach able to capture size-dependent effects. Strain gradient theory falls within this aim, and it is included into the thin plate formulation in the current paper. Following the procedure developed in Bacciocchi et al. (2020, 2021), a finite element model based on higher-order Hermite interpolating functions is used here to evaluate the mechanical behavior of laminated composite square plates with holes. These peculiar configurations cannot be solved analytically. Highlights: The mechanical behavior of laminated thin plates with holes is investigated within the nonlocal elasticity theory. A numerical scheme based on the finite element method using Hermite interpolating polynomials is developed. The results should be act as benchmarks for future developments of the numerical approaches involving the nonlocal theory.